An approach to the implementation of international legal instruments in the area of control over administration - Sinani, Blerton (Array, 2020)
In all states governed by the rule of law the administration is subject to the law and supervision by the courts on the same basis as any individual/citizen, in accordance with the principle of the supremacy of the law. The author only represents the most important instruments in the field of international law concerning control over administration, which supervise the implementation of human rights in the country that has ratified the respective instruments. Therefore, the ratification and incorporation of international normative legal instruments in the form of conventions, such as the European Convention on Human Rights within the national legal order, impose the obligation for a certain state to respect or protect the rights guaranteed by the respective Convention, as well as the case-law of the European Court of Human Rights that governs the interpretation and proper application of the Convention, the relevant European Court of Human Rights case-law setting standards for assessing the efficiency and effectiveness of public administration. Hence, this case law should act as a guideline for improving legal regulations and, under certain circumstances, avoiding the initiation of an administrative dispute before competent national courts, if objectively possible. However, due to certain reasons which will be elaborated upon in this paper, some deviations can occur and, for that matter, judicial review means review by courts of administrative action with a view to ensuring their legality as well as providing the protection and realization of the rights and legal interests of citizens in the sphere of administrative law.